Reproductive Ecology and Human Evolution
1 online resource (478 pages)
Keywords: The study of human reproductive ecology represents an important new development in human evolutionary biology. Its focus is on the physiology of human reproduction and evidence of adaptation, and hence the action of natural selection, in that domain. But at the same time the study of human reproductive ecology provides an important perspective on the historical process of human evolution, a lens through which we may view the forces that have shaped us as a species. In the end, all actions of natural selection can be reduced to variation in the reproductive success of individuals.Peter Ellison is one of the pioneers in the fast growing area of reproductive ecology. He has collected for this volume the research of thirty-one of the most active and influential scientists in the field. Thanks to recent noninvasive techniques, these contributors can present direct empirical data on the effect of a broad array of ecological, behavioral, and constitutional variables on the reproductive processes of humans as well as wild primates. Because biological evolution is cumulative, however, organisms in the present must be viewed as products of the selective forces of past environments. The study of adaptation thus often involves inferences about formative ecological relationships that may no longer exist, or not in the same form. Making such inferences depends on carefully weighing a broad range of evidence drawn from studies of contemporary ecological variation, comparative studies of related taxonomies, and paleontological and genetic evidence of evolutionary history. The result of this inquiry sheds light not only on the functional aspects of an organism's contemporary biology but also on its evolutionary history and the selective forces that have shaped it through time.Encompassing a range of viewpoints--controversy along with consensus--this far-ranging collection offers an indispensable guide for courses in biological anthropology, human biology, and primatology, along with